Advanced Applications for Smart Energy Systems Considering Grid-Interactive Demand Response - Reinders, Angèle (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book covers applied research on smart energy systems, smart grids, smart energy homes, smart energy products and services, and the advanced applications thereof, in the context of demand response and grid interactions. In particular, this book is focused on interdisciplinary research results that combine technical, social, environmental, and economic aspects of smart energy systems and smart energy products. Moreover, several chapters are based on the evaluation of real life cases, energy pilots, prototypes of smart energy products, and end user surveys and interviews.